Pathogenicity of Colletotrichum species isolates on different mango (Mangifera indica L.) varieties in Southwestern Ethiopia - Abera, Amsalu; Lemessa, Fikre; Adunga, Girma; Daba, Gerba (Journal of Postharvest Technology, 2022)
Mango (Mangifera indica L.) is one of the most popular fruits to millions of people and grown throughout the tropical and subtropical regions of the world. Colletotrichum species are the most important and prevalent pathogen causing great yield losses to mango growers in the country. Characterization of the causal agent by pathogenicity test and virulence variability of the pathogen on their host response is not well documented in southwestern part of Ethiopia. Therefore, the aims of the current study were to investigate pathogenicity of Colletotrichum species (isolates) and to assess pathogenic variability on local and commercially cultivated mango varieties in Ethiopia. Isolates of Colletotrichum species collected from nine locations in southwestern Ethiopia from mango leaves, panicles and fruit were studied for pathogenicity. Artificial inoculation of 5 varieties of Tommy Atkins, Keitt, Kent, Apple mango, Vandyke and local variety was made by wounding detached mango fruits, leaves and seedlings under greenhouse condition. The pathogenicity test result on detached mango fruits showed the presence of three virulence level among Colletotrichum isolates as highly pathogenic (62.5%), pathogenic (25%) and mildly pathogenic (12.5%). Virulent isolate tested on mango seedlings scored (13.6mm) lesion diameter. Accordingly, local mango varieties, Kent and Vandyke were categorized as susceptible varieties, while Tommy Atkins, Keitt and Apple mango varieties were intermediately susceptible. Since this result was solely based on laboratory experiment, we recommend further research to be conducted at field conditions on those varieties and including other mango varieties in the country.